"Made in China" : the ultimate warning label - Navarro, Peter (FTPress Delivers elements., 2010)
This Element is an excerpt from The Coming China Wars: Where They Will Be Fought and How They Can Be Won (ISBN: 9780132359825) by Peter Navarro. Available in print and digital formats. A matter of life or death: why you can't trust the safety of any product that's been made in China. China is flooding the world with a staggering array of cancerous, contaminated, and defective products. We've seen Barbie doll accessories decked out in "designer lead"...cough syrup and toothpaste laced with antifreeze...pajamas soaked in formaldehyde...cat and dog treats spiked with deadly melamine. These headline grabbers are but the tip of a very dangerous iceberg....